2021
DOI: 10.1371/journal.pone.0250394
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloid and acetogenin-rich fraction from Annona crassiflora fruit peel inhibits proliferation and migration of human liver cancer HepG2 cells

Abstract: Plant species from Annonaceae are commonly used in traditional medicine to treat various cancer types. This study aimed to investigate the antiproliferative potential of an alkaloid and acetogenin-rich fraction from the fruit peel of Annona crassiflora in HepG2 cells. A liquid-liquid fractionation was carried out on the ethanol extract of A. crassiflora fruit peel in order to obtain an alkaloid and acetogenin-rich fraction (AF-Ac). Cytotoxicity, proliferation and migration were evaluated in the HepG2 cells, as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…The stephalagine was purified by semi-preparative HPLC on RP-C 18 and structurally characterized by high-resolution mass spectrometry, with electrospray ionization (HR-ESI-MS) and nuclear magnetic resonance (NMR) techniques, for the first time by Pereira et al [ 29 ]. Additionally, recent studies have reported the presence of stephalagine in araticum peel and pulp [ 14 , 26 , 27 , 28 , 30 ], indicating that this compound is present in more than a fraction of the fruit. Stephalagine, an aporphine alkaloid, has demonstrated anti-obesity, antinociceptive, and anti-edematogenic effects, suggesting its use as a new potential drug [ 28 , 29 ].…”
Section: Bioactive Compounds Found In Araticum Fruit Partsmentioning
confidence: 99%
“…The stephalagine was purified by semi-preparative HPLC on RP-C 18 and structurally characterized by high-resolution mass spectrometry, with electrospray ionization (HR-ESI-MS) and nuclear magnetic resonance (NMR) techniques, for the first time by Pereira et al [ 29 ]. Additionally, recent studies have reported the presence of stephalagine in araticum peel and pulp [ 14 , 26 , 27 , 28 , 30 ], indicating that this compound is present in more than a fraction of the fruit. Stephalagine, an aporphine alkaloid, has demonstrated anti-obesity, antinociceptive, and anti-edematogenic effects, suggesting its use as a new potential drug [ 28 , 29 ].…”
Section: Bioactive Compounds Found In Araticum Fruit Partsmentioning
confidence: 99%
“…Thus, the role of Bcl-2 proteins in regulating intracellular and mitochondrial Ca 2+ homeostasis, and subsequently to several other processes such as cell migration, independently of apoptosis, is emerging [ 53 ]. Increased intracellular Ca 2+ levels have been described to be associated to the anti-migration effects of alkaloid compounds in liver cancer cells [ 54 ]. Based on this consideration, we can hypothesize that the increased migration properties observed in melanoma cells overexpressing Bcl2L10 could also be linked to the reduced [Ca 2+ ] i detected in the same cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental tests, analyses of phytocompounds such as alkaloids, present in many annonaceae (Chen et al, 2021; E.V. Costa et al, 2021;Justino et al, 2021;Kumar et al, 2021;Pandiyan & Ilango, 2022;Perrone et al, 2022;Rocha et al, 2021) that also exert antioxidant activity, were not included. In A. muricata, the strong antioxidant effect is highly correlated, mainly, to phytochemicals such as flavonoids and phenolic compounds, however, several other antioxidant compounds have been identified, such as tannins, saponins, glycoside, and acetogenins in this species (Esparza & González, 2020;Wahab et al, 2018) and other annonaceous (Andrade et al, 2021;Gowsalya & Sathya, 2021;Kumar et al, 2021;Perrone et al, 2022;Villalva et al, 2021).…”
Section: Determina On Of the An Oxidant Ac Vity Of Extractsmentioning
confidence: 99%
“…Nascimento et al, 2003). Annonaceous acetogenins constitute a series of polyketides found almost exclusively in plants of the Annonaceae family with bioactivity and mechanisms of action of scientific interest (Justino et al, 2021;Kazman et al, 2022;R.D.P. Nascimento et al, 2022;Neske et al, 2020).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation